THE EFFECT OF TRAINING AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE CLARION BREAD AND CAKE LAMPUNG - Kurniawan Pratama; Hepiana Patmarina (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The main purpose of this study is to identify the effect of training on employee performance, identify the influence of organizational citizenship behavior (OCB) on employee performance and identify the impact of training and organizational citizenship behavior (OCB) on employee performance. The quantitative method applied here using a saturated sampling technique involved all members of the population, considering the limited sample size of the study, researchers selected 60 participants from Clarion bread and cake Lampung employees. Windows version 25 of SPSS is used for data analysis. Multiple linear regression tests, reliability and validity tests, hypothesis tests (partial T tests) and (simultaneous F tests), and coefficients of determination are some of the tests performed. The data collection is collected through a google form questionnaire. The findings of this study show that training has a considerable positive influence in partially improving employee performance (t-test), and shows that organizational citizenship behavior has a considerable positive influence in partially improving employee performance (t-test). Then simultaneous testing of training and organizational citizenship behavior (Test F) also showed a significant effect on employee performance.